Clientelism in small states: how smallness influences patron–client networks in the Caribbean and the Pacific. Issue 1 (2nd January 2020) - Veenendaal, Wouter; Corbett, Jack
ABSTRACT: Studies of clientelism increasingly focus on the brokers, networks and party machines that make clientelism work in mass democracies. This article highlights the different forms clientelistic politics can take by looking at small, rather than large, democracies in the Caribbean and the Pacific. Countries in both regions experience considerable clientelistic politics, but without the same dependence on brokers, networks and party machines. Based on extensive fieldwork in 15 different Caribbean and Pacific small states, resulting in over 200 interviews, we uncover how clientelism is practised in these hitherto neglected cases. We find that the size of these states contributes to the emergence of clientelistic relations based on (1) the 'face-to-face' connections and overlapping role relations between citizens and politicians, (2) politicians' electoral dependence on a very small number of votes, and (3) enhanced opportunities for monitoring and controlling clientelistic exchanges. Smallness is furthermore found to limit, albeit not entirely dispense with, the need for brokers, networks and party machines, and to amplify the power of clients vis-à-vis their patrons, altering the nature and dynamics of clientelism in important ways. In a final section we discuss how clientelism contributes to other dominant trends in small state politics: personalism and executive domination.